2010
DOI: 10.1086/653119
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Laboratory Monitoring in Sub‐Saharan Africa: A Review of the Current Literature

Abstract: As the global community evaluates the unprecedented investment in the scale-up of HIV therapy and considers future investments in HIV care, it is crucial to identify those HIV interventions that maximize the benefit realized from each dollar spent. The use of laboratory monitoring assays – CD4 cell count and HIV RNA – in decisions about when to initiate and switch antiretroviral therapy may offer substantial clinical benefit, but their economic value remains controversial. Cost-effectiveness analysis can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…Other published models besides the three used here have also examined optimal strategies for ART monitoring, in a range of settings, and have findings that are consistent with our results 3,6,19 . One model, however, stands in contrast: Hamers et al 4 previously suggested that viral load monitoring would be cost-saving and could improve life-expectancy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Other published models besides the three used here have also examined optimal strategies for ART monitoring, in a range of settings, and have findings that are consistent with our results 3,6,19 . One model, however, stands in contrast: Hamers et al 4 previously suggested that viral load monitoring would be cost-saving and could improve life-expectancy.…”
Section: Discussionsupporting
confidence: 87%
“…Patient monitoring models were last reviewed in 2010 by Walensky et al 19 Mathematical models that have attempted to represent disease progression and monitoring are consistent with trial and observational data: immunologic monitoring offers some morbidity and mortality benefit (i.e. less time spent with clinical events, fewer deaths) over clinical monitoring, and virologic monitoring may offer some morbidity and mortality benefit over immunologic monitoring 5,6,7,8,9,10,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations for periodic CD4 counts before and throughout treatment also exist, along with suggestions for periodic viral load monitoring where available [62]. Many individual country guidelines, however, recommend only clinical monitoring due to insufficient access to routine laboratory testing [11]. Immunologic and virologic testing have widely accepted clinical benefits, and examination of the cost-effectiveness of these strategies will prove an important part of developing and implementing new monitoring strategies [61].…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effective analysis models in resource-poor settings can add guidance as to the interpretation of investment of resources to improve laboratories in developing countries. 18 Public health and policy makers must have accurate diagnoses of diseases, if they are going to effectively allocate resources for public health. Advocacy will be required to raise awareness that it is possible to improve the quality of laboratory diagnostic capability in less-developed countries to ensure their availability.…”
Section: Discussionmentioning
confidence: 99%